Pendekatan Inklusif dalam Pengabdian Tanggap Darurat Bencana untuk Memperkuat Ketahanan Sosial dan Kesehatan Lingkungan di Padang dan Pesisir Selatan: Implementation of an Inclusive Approach in Disaster Emergency Response for Social Resilience in Padang and Pesisir Selatan - Roni Ekha Putera; Tirza Haqia Purnama; Tengku Rika Valentina; Rinawati; Annisa Fitri; Yurniwati; Ratih; Billy Febrima Hidayat; Zahran Mabrukah Tomimi; Nika Saputra (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Hydrometeorological disasters in the form of floods and flash floods that struck West Sumatra Province from late November to December 2025 caused multidimensional impacts on affected communities, particularly in social conditions, environmental health, education, and psychosocial well-being among vulnerable groups. This study aims to analyze the implementation of an inclusive disaster emergency response community service program and its contribution to strengthening social resilience and environmental health in affected areas. This study employed a rapid response community service approach using rapid assessments, coordination with local governments, and short preparatory training for the implementation team. Program interventions included community-based psychosocial assistance, distribution of 400 hygiene kits, provision of 400 school kits, and brief education on clean and healthy living behaviours (PHBS). The program was implemented by Universitas Andalas in collaboration with Universitas Ekasakti and the community partner Tabik DC in Padang City and Pesisir Selatan Regency. The primary beneficiaries included children, older adults, flood-affected families, and other vulnerable groups, including students with special needs. The results indicate that the program increased children’s participation in psychosocial activities, improved social interaction at the community level, and ensured the distribution of basic hygiene and educational needs to targeted beneficiaries. In addition, local stakeholders demonstrated improved coordination capacity in implementing inclusive emergency response activities. In conclusion, the implementation of an inclusive and collaborative community service model plays a significant role in supporting early post-disaster recovery, particularly in strengthening social resilience and maintaining environmental health among vulnerable populations.